SOSIALISASI DAN SIMULASI MITIGASI BENCANA GEMPA BUMI DALAM MENINGKATKAN KESIAPSIAGAAN SISWA SDN 2 WATES PONOROGO - Risma Dwi Arisona (ASANKA : Journal of Social Science and Education, 2020)
Earthquake disasters occur suddenly without being able to be predicted by humans. By knowing that earthquakes cannot yet be scientifically predicted, efforts should be made to reduce the risk of the consequences of the earthquake. The cause of the large number of victims of earthquake disasters due to lack of knowledge and earthquake disaster preparedness. Therefore, it is important to socialize and simulate earthquake mitigation early to minimize the risk of becoming a victim through disaster education in schools. Education is an effective vehicle for building student behavior in the face of disasters. Knowledge possessed by students can influence the attitude of earthquake disaster preparedness. This research is a practical research with limitation of the problem through the provision of material and training in earthquake disaster mitigation simulation. The results showed that: 1) The material presented was interesting, there was very significant knowledge about the types of disasters, disaster symbols, and preparedness procedures before, when they occurred, and after the earthquake disaster; 2) Adding knowledge and skills in self-rescue in the event of an earthquake; 3) Practicing reflexes in taking steps to save themselves when an earthquake suddenly occurs, 4) Increasing earthquake preparedness for elementary school students and teachers.